2022
DOI: 10.1155/2022/3300363
|View full text |Cite
|
Sign up to set email alerts
|

Developing Students’ Mathematical Critical Thinking Skills Using Open-Ended Questions and Activities Based on Student Learning Preferences

Abstract: This study has two parts: phase I designed activities to support all students’ learning preferences, and phase II used open-ended questions and activities based on these preferences to develop students’ mathematical critical thinking skills in polynomials at all performance levels (i.e., high-achieving, fair-achieving, and low-achieving students). This research used an embedded mixed-method design. The subjects selected were 28 out of 98 seventh graders at a boys’ junior high school in Bangkok, Thailand, who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Moreover, conceptual understanding, questioning, and investigation are used for the development of curiosity, which is needed for higher-order thinking skills development (Mulyati et al, 2021). Open-ended questions also provide a mindset thought-provoking that is illustrated in the textbook and also supported by the findings of Monrat et al (2022) who are of the view that open-ended questions can be used in developing mathematical critical thinking skills.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, conceptual understanding, questioning, and investigation are used for the development of curiosity, which is needed for higher-order thinking skills development (Mulyati et al, 2021). Open-ended questions also provide a mindset thought-provoking that is illustrated in the textbook and also supported by the findings of Monrat et al (2022) who are of the view that open-ended questions can be used in developing mathematical critical thinking skills.…”
Section: Discussionmentioning
confidence: 70%
“…It is also claimed to be the foundation for effectively training 21st-century skills (Preus, 2012). The ways teachers diversify authentic problems into additional preferences (tastes) when students learn (Monrat, Phaksunchai, & Chonchaiya, 2022). Fourth, continue to encourage interaction between students during the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Authentic learning plays a crucial role in employing effective teaching techniques that foster 21 st -century skills, including critical thinking. Students at every educational level appreciate a diverse range of genuine problems that offer real-world applications within their learning experiences (Monrat, Phaksunchai, & Chonchaiya, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Firdaus, Kailani, Bakar, and Bakry (2015), this approach involves multilateral interactions between learners and teachers, with the instructor facilitating the process. Monrat et al (2022) found that learners exhibited higher motivation to acquire knowledge when immersed in an environment that prioritized active engagement and collaborative interaction, while Syafril, Aini, Pahrudin, and Yaumas (2020) suggested that interactivity in the classroom could help build students' enthusiasm for learning and support their critical thinking abilities.…”
Section: Discussionmentioning
confidence: 99%